Single crystal type polyvalent positive electrode material and its manufacturing method, lithium ion battery

By filling the polycrystal particles of the quasi-single-crystal particles of the multivalent battery cathode material, the problem of unstable particle boundaries of the cathode material in the prior art is solved, and the cycle life and rate performance of the battery is significantly improved.

JP2025514451AActive Publication Date: 2025-05-02BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024564625
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-05-02
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

In the prior art, the particle boundaries of the positive electrode material of the multivalent battery are unstable, resulting in a decrease in electrochemical performance, including battery capacity, cycle performance and safety performance.

Method used

A single crystal multivalent battery positive electrode material is used, which includes polycrystal particles of quasi-single-crystal particles, and there is a G element at the particle boundary. The concentration of G element gradually decreases from the particle boundary to the surface. G element can be selected such as Ni, Co, Mn.

Benefits of technology

By filling the G element at the particle boundary, the particle boundary stability of the positive electrode material is significantly improved, the cycle life of the battery is extended, the energy density and rate performance is improved, and the internal impedance increase rate of the battery is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514451000001_ABST
    Figure 2025514451000001_ABST
Patent Text Reader

Abstract

A single crystal type polyvalent positive electrode material and its manufacturing method and a lithium ion battery are disclosed. The polyvalent positive electrode material includes quasi-single crystal particles consisting of a plurality of crystal grains, and a G element is present at the grain boundary between the crystal grains, and the concentration of the G element at the g site of the grain boundary gradually decreases as the distance between the g site and the surface of the quasi-single crystal particle increases, and the G element is selected from at least one of Ni, Co, Mn, Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er and B. The single crystal type polyvalent positive electrode material having the above special structure significantly reduces the erosion of the grain boundary by the electrolyte, improves the grain boundary stability of the positive electrode material, and significantly improves the cycle life, energy density, rate performance, impedance increase rate, etc. of a lithium ion battery including the positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of lithium ion battery technology, and in particular to a monocrystalline polyvalent positive electrode material and a method for producing the same, and a lithium ion battery. [Background technology]

[0002] With the rapid development of the new energy industry, the market has placed higher requirements on the performance of lithium-ion batteries. As the core material that has the greatest impact on battery performance, the positive electrode material is improved towards the goals of high energy density, long cycle life, high safety and low cost. Polyvalent materials such as nickel cobalt manganese oxide (NCM) and nickel cobalt aluminate (NCA) have become one of the most widespread positive electrode materials due to their excellent energy density advantages. In order to achieve higher specific capacity, the Ni content in the polyvalent material is constantly increasing, which reduces the stability of the material, and the cycle life and safety performance are correspondingly worsened. Therefore, the application of more stable single-crystalline nickel cobalt manganese oxide materials is becoming more widespread.

[0003] According to the crystal growth arrangement, single crystal polyvalent materials can be divided into two states: one is a pure single crystal state, in which each single crystal grain is an independent crystal grain; the other is a quasi-single crystal state, in which multiple crystal grains are bonded together. There are no vacancies or interfaces inside the pure single crystal grains, and the Li +The current conventional commercial single crystal materials contain different proportions of the pure single crystal particles and quasi-single crystal particles because the pathways for the release and absorption of oxygen are long and the capacity and rate performance of the material are both poor. However, as described in the article "Accelerated Degradation in a Quasi-Single-Crystalline Layered Oxide Cathode for Lithium-Ion Batteries Caused by Residual Grain Boundaries" published by Zhang et al. in Nano Letters in 2022, such quasi-single crystal particles have relatively concentrated anisotropic stress at the grain boundaries where different crystal grains are connected to each other due to the change in the crystal cell volume caused by the H2-H3 phase transformation during the charge and discharge cycle, which causes interlayer slip, dislocations and stacking faults at the grain boundaries, accelerating the loss of active oxygen and irreversible phase transformation, and reducing the electrochemical capacity. In addition, the stress concentration causes the particles to crack along the grain boundaries, generating new highly active surfaces, which further accelerate the side reactions between the material and the electrolyte, causing problems such as a decrease in cycle life and an increase in resistance.

[0004] Common methods for improving the stability of materials include bulk doping, surface coating, etc., but conventional technical means mainly deal with the stabilization treatment of the internal structure of the material crystal and the particle surface, and there is no effective means for the degradation problem of grain boundaries of quasi-single crystal particles. Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention aims to provide a single-crystal polyvalent positive electrode material and a manufacturing method thereof, and a lithium-ion battery, in order to overcome the problem of deterioration of electrochemical performance such as battery capacity and rate performance due to poor grain boundary stability of quasi-single crystal positive electrode material particles existing in the prior art. The single-crystal polyvalent positive electrode material includes quasi-single crystal particles consisting of a plurality of crystal grains, and a G element is present at the grain boundaries between the crystal grains. The concentration of the G element at the g site of the grain boundary gradually decreases as the distance between the g site and the surface of the quasi-single crystal particle increases, thereby significantly mitigating the erosion of the grain boundaries by the electrolyte, improving the grain boundary stability of the positive electrode material, and significantly improving the cycle life, energy density, rate performance and impedance increase rate of a lithium-ion battery including the positive electrode material. [Means for solving the problem]

[0006] In order to achieve the above object, a first aspect of the present invention provides a single-crystal polyvalent positive electrode material, the polyvalent positive electrode material including quasi-single-crystal particles consisting of a plurality of crystal grains, and a G element is present at the grain boundaries between the crystal grains; The concentration of G elements at the g sites of the grain boundaries gradually decreases as the distance between the g sites and the surface of the quasi-single crystal grain increases. The G element is characterized by being selected from at least one of Ni, Co, Mn, Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er and B.

[0007] A second aspect of the present invention provides a method for producing a monocrystalline polyvalent positive electrode material, the method comprising the steps of: The method includes a step of mixing a multivalent positive electrode material matrix with a grain boundary stabilizer containing a G element, and then sintering the mixture to obtain the single crystal multivalent positive electrode material; The G element is selected from at least one of Ni, Co, Mn, Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, Ba, and B; The grain boundary stabilizer has a D50 of 0.01-10 μm, and the D10, D50 and D90 of the grain boundary stabilizer satisfy K90=(D90-D10) / D50≧1.5.

[0008] A third aspect of the present invention provides a single crystal type polyvalent positive electrode material produced by the above-mentioned production method.

[0009] A fourth aspect of the present invention provides a lithium ion battery comprising the above-mentioned single crystal polyvalent positive electrode material.

[0010] By the above technical means, the monocrystalline polyvalent positive electrode material and the manufacturing method thereof, and the lithium ion battery according to the present invention have the following beneficial effects.

[0011] The monocrystalline polyvalent positive electrode material according to the present invention comprises quasi-single crystal particles consisting of a plurality of crystal grains, and G element exists at the grain boundary between the crystal grains, and the concentration of G element at the g site of the grain boundary gradually decreases as the distance between the g site and the surface of the quasi-single crystal particle increases, and the G element is fully permeated and filled into the grain boundary of the positive electrode material, which reduces the stress concentration generated at the grain boundary of the positive electrode material due to the change in the volume of the crystal cell during charging and discharging, improves the grain boundary stability of the positive electrode material, and significantly improves the cycle life of the lithium ion battery containing the positive electrode material, and at the same time, improves the grain boundary stability and reduces the occurrence of new internal interfaces due to the fewer grain boundary cracks, and reduces the impedance increase rate of the lithium ion battery containing the positive electrode material under multiple cycling and long-term storage conditions. Specifically, compared with the conventional positive electrode material, the lithium ion battery containing the positive electrode material according to the present invention has a cyclic capacity retention rate of at least 4% and an impedance increase rate of at least 15% when half-charged and discharged at 1C for 80 cycles under 45°C conditions.

[0012] Furthermore, in the single crystal type multivalent positive electrode material according to the present invention, the gradient packing of the G element at the grain boundary position functions as a conductive medium, and Li +The outward diffusion of the positive electrode material is advantageous, and when the positive electrode material is used in a lithium ion battery, the capacity is fully exerted and the rate performance is better. Specifically, compared with the conventional positive electrode material, the 0.1C discharge capacity of the lithium ion battery using the positive electrode material of the present invention can be improved by more than 1mAh / g in the voltage range of 3.0-4.3V under the condition of 25°C, and the discharge at 1C rate can be improved by more than 2%.

[0013] The method for producing the monocrystalline polyvalent positive electrode material according to the present invention is simple, easy to control, and suitable for industrial production. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a schematic diagram showing a quasi-single crystal particle of a single crystal type multivalent positive electrode material according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing that the grain boundary stabilizer cobalt hydroxide used in Example 1 contains micron and submicron ions. [Diagram 3] 1 is a schematic cross-sectional view of a single crystal type multivalent positive electrode material produced in Example 1, and the numbers in the figure are examples of measurement sites for element concentrations within grain boundaries. [Figure 4] 1 is a graph showing the cycle performance comparison of the positive electrode materials prepared in Preparation Example 1, Example 1 and Comparative Example 1 at a 1C rate, where the test temperature is 45° C. and the voltage range is 3.0-4.3V. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The endpoints of the ranges and any values ​​disclosed herein should be understood not to be limited to such exact ranges or values, but to include values ​​close to these ranges or values. In the case of ranges of numerical values, the endpoints of each range, and the endpoints of each range and any single point value, and the single point values ​​may be combined with each other to obtain one or more new numerical ranges, and these numerical ranges are deemed to be specifically disclosed in the specification.

[0016] A first aspect of the present invention provides a single-crystal polyvalent positive electrode material, the polyvalent positive electrode material including quasi-single-crystal particles consisting of a plurality of crystal grains, and a G element is present at a grain boundary between the crystal grains; The concentration of G elements at the g sites of the grain boundaries gradually decreases as the distance between the g sites and the surface of the quasi-single crystal grain increases. The G element is characterized by being selected from at least one of Ni, Co, Mn, Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er and B.

[0017] In the present invention, the grain boundary refers to the contact interface and / or gap between multiple crystal grains constituting a quasi-single crystal particle. In the present invention, since a large amount of crystal nuclei are obtained by co-development of a single crystal type multivalent positive electrode material, most of the crystal grains fuse together during the crystal growth process, and when the crystal grows to a certain size, that is, when the single crystal type multivalent positive electrode material described in the present invention is formed, some crystal grains are not completely fused, and the orientation of these crystal grains is different, and the interface is the grain boundary described in the present invention.

[0018] In the present invention, the monocrystalline polyvalent positive electrode material includes quasi-single crystal particles consisting of a plurality of crystal grains, and G element is present at the grain boundaries between the crystal grains. The concentration of G element at the g site of the grain boundary gradually decreases as the distance between the g site and the surface of the quasi-single crystal particle increases. The G element is sufficiently permeated and filled into the grain boundaries of the positive electrode material, which reduces the stress concentration generated at the grain boundaries of the positive electrode material due to the change in the crystal cell volume during charging and discharging cycles, improves the grain boundary stability of the positive electrode material, and significantly improves the cycle life of a lithium ion battery including the positive electrode material. At the same time, the improved grain boundary stability and fewer grain boundary cracks reduce the occurrence of new internal interfaces, and the impedance increase rate of a lithium ion battery including the positive electrode material is lower under multiple cycles and long-term storage conditions.

[0019] Furthermore, the G element is at least one selected from the group consisting of Mn, Co, W, La, Al, Ti, Zr and Nb.

[0020] According to the present invention, in an SEM image of a cross-sectional sample of the quasi-single crystal grain, the concentration of the G element at the g site at the grain boundary satisfies the following relationship: 1.2C1≧C g ≧0.8C2 formula I

number

[0021] In the present invention, L is the total length of the grain boundary passing through the g site, which means the sum of the approximate lengths of the two shortest grain boundary sections that start from the g site and extend along two opposite directions parallel to the crystal plane to the surface of the quasi-single crystal grain. g means the approximate length of the shortest grain boundary path that starts at the g site and extends along a direction parallel to the grain boundary to the surface of the quasi-single crystal grain.

[0022] In the present invention, L and L g The reason why approximate values ​​were used in all of the above is that the grain boundary flow is not a straight line and cannot be measured, so a simulation was performed by drawing multiple straight lines along the grain boundary flow, and the actual length of the grain boundary was approximately replaced by the length of the straight lines.

[0023] In the present invention, C1, C2 and C gwas measured by scanning electron microscope spectroscopy. A cross-sectional sample was prepared from the single crystal polyvalent positive electrode material by ion milling, and a scanning electron microscope spectroscopy analyzer was used to select quasi-single crystal grains in the cross-sectional sample, and energy spectrum analysis points were tested at different sites of the grain boundaries to obtain the atomic percentage of elements at the sites, and at least five sets of data were tested for each position and the average value was taken.

[0024] In the present invention, in order to embody the concentration change trend of the G element, multiple different sites along the grain boundary are randomly selected for testing and evaluation, and the selected sites should be relatively distributed to avoid excessive concentration.

[0025] Due to limitations in the stability of the detection method, there may be individual abnormal data that exceed the calculation results of Formula II, and these should be eliminated during evaluation. If 75% or more of the data meets the rule that the concentration of the G element at the g site of the grain boundary described in the present invention gradually decreases as the distance between the g site and the surface of the quasi-single crystal particle increases, it should be considered as meeting the technical effects and required scope of the present invention.

[0026] Furthermore, 1.1C1 ≥ C g ≧0.9C2.

[0027] According to the present invention, the total length L of the grain boundary satisfies 0.01 μm≦L≦8 μm according to spectroscopic analysis using a scanning electron microscope.

[0028] According to the present invention, C1-C2≧0.1%.

[0029] Furthermore, C1-C2 ≧ 0.2%.

[0030] According to the present invention, when C1>5%, the value range of k is 0.9 to 1.1, and when C1≦5%, the value range of k is 0.8 to 1.2.

[0031] As shown in FIG. 1, FIG. 1 is a schematic diagram of a quasi-single crystal particle of a single crystal type polyvalent positive electrode material according to the present invention. As can be seen from FIG. 1, the positive electrode material according to the present invention includes a quasi-single crystal particle consisting of a plurality of crystal grains as shown in the figure, and the contact surface between each crystal grain is the grain boundary according to the present invention. Taking the g site in the figure as an example, the total length L of the grain boundary from the g site to the surface of the quasi-single crystal particle along the grain boundary includes two parts in the L1, L2 direction and the L3, L4 direction, and the value of the total length L can be obtained by L1+L2+L3+L4. The g site is the shortest path length L along the grain boundary direction to the surface of the quasi-single crystal particle. g can be obtained by L3+L4, the concentration C1 of the G element on the surface of the quasi-single crystal grain is obtained by testing at different positions on the surface and taking the average value, and the concentration C2 of the G element in the bulk phase of the quasi-single crystal grain is obtained by testing at central positions inside different crystal grains and taking the average value.

[0032] According to the present invention, the major axis D1 of the quasi-single crystal particle satisfies 0.1 μm≦D1≦20 μm, and the minor axis D2 thereof satisfies 0.1 μm≦D2≦20 μm.

[0033] According to the present invention, the major axis D3 of the crystal grain satisfies 0.1 μm≦D3≦12 μm, and the minor axis D4 of the crystal grain satisfies 0.1 μm≦D4≦12 μm.

[0034] According to the present invention, the grain boundary has a width of 1 to 50 nm, and the difference between the maximum value of the grain boundary width and the minimum value of the grain boundary width is 20 nm or less.

[0035] In the present invention, the grain boundary width is the distance between the surfaces of adjacent grains on both sides of the grain boundary along the surface direction of the material. The grain boundary width is measured by scanning electron microscopy. When the difference between the maximum grain boundary width and the minimum grain boundary width exceeds 20 nm, the concentration of the G element at the wide grain boundary site increases relatively, and the concentration of the G element at the site does not apply to the formula shown in Formula II.

[0036] In the present invention, the addition of the grain boundary stabilizer does not change the difference between the total length L of the grain boundaries, the major axis D1 of the quasi-single crystal particles, the minor axis D2 of the quasi-single crystal particles, the major axis D3 of the crystal grains, the minor axis D4 of the crystal grains, the width (H) of the grain boundaries, and the maximum value (H max ) and the minimum value (H min ) of the width of the grain boundaries. The difference between the total length L of the grain boundaries, the major axis D1 of the quasi-single crystal particles, the minor axis D2 of the quasi-single crystal particles, the major axis D3 of the crystal grains, the minor axis D4 of the crystal grains, the width (H) of the grain boundaries, and the maximum value (H max ) and the minimum value (H max ) of the width of the grain boundaries of the single-crystalline type polyvalent cathode material is the same as that of the polyvalent cathode matrix material before the mixed sintering of the grain boundary stabilizer.

[0037] In the present invention, the total length L of the grain boundaries, the major axis D1 of the quasi-single crystal particles, the minor axis D2 of the quasi-single crystal particles, the major axis D3 of the crystal grains, the minor axis D4 of the crystal grains, the width (H) of the grain boundaries, the maximum value (H max ) and the minimum value (H max ) of the width of the grain boundaries in the polyvalent cathode material are measured by SEM. Specifically, in the SEM image of the polyvalent cathode material, 300 quasi-single crystal particles of the polyvalent cathode material are randomly selected as samples, and the average value is obtained.

[0038] According to the present invention, the single-crystalline type polyvalent cathode material includes a matrix and a coating layer coated on the matrix, the matrix has a structure as shown in Formula III, Li 1+a (Ni x Co y Me z M w )O2 Formula III where -0.1 ≦ a ≦ 0.1, 0 < x < 1, 0 < y ≦ 0.4, 0 < z ≦ 0.6, 0 ≦ w ≦ 0.2, Me is selected from Mn and / or Al, and M is selected from at least one element of Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, and Ba, the coating layer is selected from a lithium oxygen compound of element G and / or an oxide of element G, G is at least one element selected from the group consisting of Ni, Co, Mn, Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, and B; The molar ratio of the coating layer in terms of n(G) to the matrix in terms of [n(Ni)+n(Co)+n(Me)+n(M)] is 0.001 to 0.05.

[0039] Furthermore, -0.06≦a≦0.06, 0.4 <x<1、0<y≦0.3、0<z≦0.5、0<w≦0.1とする。

[0040] Furthermore, Me is selected from Mn and / or Al.

[0041] Furthermore, M is at least one element selected from the group consisting of W, La, Al, Y, Ti, Zr, Nb, Ce, Mg, and Sr.

[0042] Furthermore, G is at least one element selected from the group consisting of Mn, Co, W, La, Al, Ti, Zr, and Nb.

[0043] Furthermore, the molar ratio of the coating layer in terms of n(G) to the matrix in terms of [n(Ni)+n(Co)+n(Me)+n(M)] is 0.005-0.04.

[0044] A second aspect of the present invention provides a method for producing a polyvalent single crystal cathode material, the method comprising the steps of: The method includes a step of mixing a multivalent positive electrode material matrix with a grain boundary stabilizer containing a G element, and then sintering the mixture to obtain the single crystal multivalent positive electrode material; The G element is selected from at least one of Ni, Co, Mn, Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, Ba, and B; The grain boundary stabilizer has a D50 of 0.01-10 μm, and the D10, D50 and D90 of the grain boundary stabilizer satisfy K90=(D90-D10) / D50≧1.5.

[0045] In the present invention, the matrix of the polyvalent positive electrode material and the grain boundary stabilizer containing the G element having a specific particle size and particle size distribution are mixed and sintered to obtain the monocrystalline polyvalent positive electrode material according to the first embodiment of the present invention. Specifically, the positive electrode material includes quasi-single crystal particles consisting of a plurality of crystal grains, the G element exists at the grain boundary between the crystal grains, and the concentration of the G element at the g site of the grain boundary gradually decreases as the distance between the g site and the surface of the quasi-single crystal particle increases, and the G element is sufficiently permeated and filled into the grain boundary of the positive electrode material, which reduces the stress concentration generated at the grain boundary of the positive electrode material due to the change in the crystal cell volume during charging and discharging cycles, improves the grain boundary stability of the positive electrode material, and significantly improves the cycle life of the lithium ion battery containing the positive electrode material. At the same time, the grain boundary stability is improved and the grain boundary crack phenomenon is reduced, which reduces the occurrence of new internal interfaces, and the impedance increase rate of the lithium ion battery containing the positive electrode material is lower under the conditions of multiple cycles and long-term storage.

[0046] In particular, the method for producing the monocrystalline polyvalent positive electrode material according to the present invention involves a simple process, is easy to control, and is suitable for industrial production.

[0047] Furthermore, the G element is at least one selected from the group consisting of Mn, Co, W, La, Al, Ti, Zr and Nb.

[0048] Furthermore, the grain boundary stabilizer is selected from at least one of oxides, oxyhydroxides, hydroxides, fluorides, sulfates, nitrates, carbonates, and oxalates containing a G element.

[0049] Furthermore, the grain boundary stabilizer has a D50 of 0.1 to 8 μm, and the D10, D50 and D90 of the grain boundary stabilizer satisfy K90=(D90-D10) / D50≧2.

[0050] According to the present invention, the specific surface area of ​​the grain boundary stabilizer is 10 m 2 / g or more.

[0051] In the present invention, the use of an interfacial stabilizer with a large specific surface area is advantageous for uniform dispersion with the material during the mixing process with the material, and the high specific surface area of ​​the interfacial stabilizer can achieve higher reaction activity and is advantageous for diffusion into the grain boundaries during the sintering process, so that the interfacial stabilizer can achieve a better grain boundary gradient filling effect.

[0052] Furthermore, the specific surface area of ​​the grain boundary stabilizer is 20-100 m 2 / g.

[0053] According to the present invention, the grain boundary stabilizer is added in an amount such that the stoichiometric ratio is 0.001≦n(G)n[n(Ni)+n(Co)+n(Me)+n(M)]≦0.05.

[0054] In the present invention, if the amount of grain boundary stabilizer used is too low, i.e., n(G) / [n(Ni)+n(Co)+n(Me)+n(M)] is less than 0.001, the added ratio of G element is too low and the gradient effect cannot be realized. If the amount of grain boundary stabilizer used is too high, i.e., n(G) / [n(Ni)+n(Co)+n(Me)+n(M)] is greater than 0.05, the G element will be excessively deposited on the particle surface, thereby suppressing the electrochemical activity of the multivalent positive electrode material, and the excess G element will generate more active Li. + Therefore, the capacity of a battery containing the polyvalent positive electrode material is reduced due to consumption of the G element. By controlling the amount of the grain boundary stabilizer used to satisfy the above range, an optimal gradient change in the grain boundary concentration of the G element can be achieved, thereby realizing the technical effect of the present invention.

[0055] Furthermore, the grain boundary stabilizer is added in an amount such that the stoichiometric ratio is 0.005≦n(G) / [n(Ni)+n(Co)+n(Me)+n(M)]≦0.04.

[0056] In the present invention, when two or more types of grain boundary stabilizers and a multivalent positive electrode material matrix are mixed to produce a single crystal type multivalent positive electrode material, the amount of each of the various grain boundary stabilizers used is not particularly limited, and the total amount of the grain boundary stabilizers added may be within the above range.

[0057] According to the present invention, the mixing conditions include mixing in a device including a stirring paddle, and the linear velocity of the end of the blade of the stirring paddle is 20 m / s or more.

[0058] In the present invention, mixing under the above conditions provides high mixing strength and ensures sufficient and uniform mixing of the grain boundary stabilizer and the polyvalent positive electrode material, while at the same time providing the grain boundary stabilizer with a certain polishing effect, causing the fine powder therein to aggregate at the grain boundaries on the surfaces of the quasi-single crystal particles, making it easier for them to penetrate and fill the grain boundaries during the sintering process.

[0059] In the present invention, the equipment containing the stirring paddle is not limited as long as the equipment contains a stirring paddle, and can be, for example, a stirring paddle rotary mixer such as a plowshare mixer, a high-speed mixer, or a mechanical blender.

[0060] In the present invention, the linear velocity v at the end of the blade = blade diameter x π x rotation speed.

[0061] Further, the mixing conditions include mixing in a device including a stirring paddle, and a linear velocity at the end of the blade of the stirring paddle is 30 to 50 m / s.

[0062] According to the present invention, the sintering conditions include a sintering temperature of 400° C. or more and a sintering time of 4 hours or more.

[0063] In the present invention, when sintering is performed under the above conditions, effective diffusion and reaction of the grain boundary stabilizer can be achieved, sufficient depth into the grain boundary can be ensured, and the effect of gradient filling can be formed. If the temperature is too low or the time is too short, the grain boundary stabilizer cannot be fully reacted, and the technical effect of the present invention cannot be achieved. If the temperature is too high or the time is too long, it will cause changes in the crystal structure of the polyvalent material, and the performance of the positive electrode material will be lost.

[0064] Further, the sintering conditions include a sintering temperature of 600 to 900° C. and a sintering time of 6 to 10 hours.

[0065] In the present invention, the type of the polyvalent cathode material is not particularly limited. Conventional polyvalent cathode materials in this field are preferably lithium nickel cobalt manganese oxide cathode materials and / or lithium nickel cobalt aluminate cathode materials.

[0066] In a specific embodiment of the present invention, the polyvalent cathode material matrix has a structure as shown in Formula IV, Li 1+a (Ni x Co y Me z M w )O2 Formula IV where -0.1 ≦ a ≦ 0.1, 0 < x < 1, 0 < y ≦ 0.4, 0 < z ≦ 0.6, 0 ≦ w ≦ 0.2, Me is selected from Mn and / or Al, and M is at least one of Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, and Ba.

[0067] Furthermore, -0.06 ≦ a ≦ 0.06, 0.4 < x < 1, 0 < y ≦ 0.3, 0 < z ≦ 0.5, 0 < w ≦ 0.1.

[0068] Furthermore, Me is selected from Mn and / or Al.

[0069] Furthermore, M is selected from at least one of W, La, Al, Y, Ti, Zr, Nb, Ce, Mg, and Sr.

[0070] In the present invention, the origin of the polyvalent cathode material matrix is not particularly limited and can be purchased on the market or made by oneself. The manufacturing method of the polyvalent cathode material is not particularly limited and can be manufactured by conventional manufacturing methods in this field.

[0071] In a specific embodiment of the present invention, the polyvalent cathode material matrix is manufactured by a step of obtaining the polyvalent cathode material by mixing a cathode material precursor, a lithium source, and a dopant and then performing heat treatment.

[0072] In the present invention, the cathode material precursor has a structure as shown in Formula V, Ni x Co y Me z (OH)2 Formula V where 0 < x < 1, 0 < y ≤ 0.4, 0 < z ≤ 0.6, and Me is selected from Mn and / or Al.

[0073] In the present invention, the lithium source may be a conventional lithium source in this field, such as Li2CO3 and / or LiOH, etc.

[0074] In the present invention, the dopant is a compound containing M, and M is selected from at least one element of Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, and Ba.

[0075] In the present invention, depending on the usage amounts of the lithium source and the cathode material precursor, 0.9 ≤ n(Li) / [n(Ni) + n(Co) + n(Me) + n(M)] ≤ 1.1, and preferably, 0.94 ≤ n(Li) / [n(Ni) + n(Co) + n(Me) + n(M)] ≤ 1.06.

[0076] In the present invention, depending on the usage amounts of the dopant and the cathode material precursor, 0 ≤ n(M) / [n(Ni) + n(Co) + n(Me) + n(M)] ≤ 0.2, and preferably, 0 ≤ n(M) / [n(Ni) + n(Co) + n(Me) + n(M)] ≤ 0.1.

[0077] In the present invention, the dopant is mixed with Ni, Co, and Me in the cathode material precursor, so that n(Ni) + n(Co) + n(Me) + n(M) = 1 in the obtained cathode material. However, when the usage amount of the dopant is low, its content cannot be accurately detected by conventional detection means. At this time, the influence of the ratio of the doping element M to Ni, Co, and Me is small, and n(Ni) + n(Co) + n(Me) + n(M) in the expression is slightly larger than 1.

[0078] In the present invention, the heat treatment conditions include a heat treatment temperature of 850 to 950° C. and a heat treatment time of 8 to 10 hours.

[0079] A third aspect of the present invention provides a single crystal type polyvalent positive electrode material produced by the above-mentioned production method.

[0080] A fourth aspect of the present invention provides a lithium ion battery comprising the above-mentioned single crystal polyvalent positive electrode material.

[0081] The present invention will now be described in detail with reference to examples. The composition of the single crystal polyvalent positive electrode material was determined by inductively coupled plasma spectroscopy. The concentration of the G element in the single crystal polyvalent positive electrode material is measured by a scanning electron microscope spectroscopic analysis method. The grain boundary length, grain boundary width, major axis, and minor axis of the quasi-single crystal grains in the single crystal type polyvalent positive electrode material are measured by scanning electron microscopy. The major and minor axes of the crystal grains in the single crystal type polyvalent positive electrode material are measured by scanning electron microscopy. The D10, D50, and D90 of the grain boundary stabilizer are measured by the laser diffraction method GB / T 19077-2016. The specific surface area of ​​grain boundary stabilizer is measured by testing GB-T19587-2017 with BET method, The cycle life, energy density and rate performance of the lithium-ion battery are tested using a 2025-type buckled battery. The manufacturing process of the 2025 type buckle battery is as follows: Manufacture of electrode sheet: A polyvalent positive electrode material, acetylene black, and polyvinylidene fluoride (PVDF) are thoroughly mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 95:3:2 to form a uniform slurry, which is then coated on aluminum foil and dried at 120 °C for 12 h. The aluminum foil is then press molded under a pressure of 100 MPa to produce a positive electrode sheet with a diameter of 12 mm and a thickness of 120 μm. The amount of the polyvalent positive electrode material carried is 15 to 16 mg / cm. 2 It is.

[0082] Battery assembly: In a gas glove box filled with argon gas with a water and oxygen content of less than 5 ppm each, the positive electrode sheet, separator, negative electrode sheet and electrolyte were assembled into a 2025-type buckle-type battery and then left to stand for 6 hours. The negative electrode sheet was a metallic lithium sheet with a diameter of 17 mm and a thickness of 1 mm, the separator was a polyethylene porous film (Celgard 2325) with a thickness of 25 μm, and the electrolyte was a mixture of 1 mol / L LiPF6, equal amounts of ethylene carbonate (EC) and diethyl carbonate (DEC).

[0083] Electrochemical performance test, In the following examples and comparative examples, [ka] The electrochemical performance test was conducted on the 2025 buckle type battery using the Nitto battery test system, and the 0.1C charge and discharge current density was 200mA / g. The charge / discharge voltage range is controlled to 3.0-4.3V, and the buckled battery is charged / discharged at room temperature at 0.1C to evaluate the initial discharge specific capacity of the multivalent positive electrode material. Cycle performance test: The charge / discharge voltage range is controlled at 3.0-4.3V, and the temperature is constant at 45°C. The buckled battery is cycled at 0.1C for two cycles of charge / discharge, and then cycled at 1C for 80 cycles to evaluate the high-temperature capacity retention rate of the multi-valent positive electrode material.

[0084] Rate performance test: The charge / discharge voltage range is controlled to 3.0-4.3V, and the buckled battery is charged / discharged twice at 0.1C at room temperature, and then charged / discharged once each at 0.2C, 0.33C, 0.5C and 1C, and the rate performance of the multivalent positive electrode material is evaluated by the ratio of the first discharge specific capacity at 0.1C to the discharge specific capacity at 1C. The first discharge specific capacity at 0.1C is the discharge specific capacity of the first cycle of the buckled battery, and the discharge specific capacity at 1C is the discharge specific capacity of the sixth cycle of the buckled battery.

[0085] Impedance increase rate test: The charge / discharge voltage range is controlled at 3.0~4.3V, the buckled battery is charged at 0.1C at room temperature, and the HPPC-DCR at 50% SOC is tested. The initial resistance is R1. The buckled battery is then charged and discharged twice at 0.1C at a constant temperature of 45℃, and then charged and discharged 80 times at 1C. After cycling, the buckled battery is charged at 0.1C at room temperature, and the HPPC-DCR at 50% SOC is tested. The resistance after cycling is R2. The impedance increase rate of the material is calculated according to the formula (R2-R1) / R1×100%.

[0086] Manufacturing Example This is to illustrate a method for producing a multivalent positive electrode material.

[0087] Manufacturing Example 1 Ni 0.6 Co 0.2 Mn 0.2 The (OH)2 precursor, the lithium source Li2CO3, LiOH and the dopant Al-containing compound are mixed in the molar ratios of n(Li) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=1.05 and n(Al) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.1, and then heat-treated at 900°C for 10h to obtain the multivalent positive electrode material P1, the composition of which is Li 1.05 Ni 0.54 Co 0.18 Mn 0.18 Al 0.1 It's O2.

[0088] Manufacturing Example 2 Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor, the lithium source LiOH and the dopant Zr-containing compound are mixed in the molar ratios of n(Li) / [n(Ni)+n(Co)+n(Mn)+n(Zr)]=1.05 and (n(Zr) / [n(Ni)+n(Co)+n(Mn)+n(Zr)]=0.002, and then heat-treated at 850°C for 10h to obtain the multivalent positive electrode material P2, the composition of which is Li 1.05 Ni 0.8 Co 0.1 Mn 0.1 Zr 0.002 It's O2.

[0089] Production Example 3 Ni 0.96 Co 0.02 Al 0.02 The (OH)2 precursor, the lithium source LiOH and the dopant Ti-containing compound are mixed with n(Li) / [n(Ni)+n(Co)+n(Al)+n(Ti)]=1.03 and n(Ti) / [n(Ni)+n(Co)+n(Al)+n(Ti)]=0.001, and then heat treated at 800°C for 10h to obtain the multivalent positive electrode material P3, the composition of which is Li 1.03 Ni 0.96 Co 0.02 Al 0.02 Ti 0.001 It's O2.

[0090] Production Example 4 Ni 0.6 Co 0.2 Mn 0.2 The (OH)2 precursor, lithium source Li2CO3 and LiOH are mixed in a molar ratio of n(Li) / [n(Ni)+n(Co)+n(Mn)]=1.05, and then heat treated at 900 °C for 10 h. The multivalent positive electrode material P4 is obtained by preparation, and its composition is Li 1.05 Ni 0.6 Co 0.2 Mn 0.2 It's O2.

[0091] The total length L of the grain boundary in the multivalent positive electrode material in the manufacturing example, the width (H) of the grain boundary, and the maximum width (H max ) and minimum value (H min ), the major axis D1 and minor axis D2 of the quasi-single crystal particles, and the major axis D3 and minor axis D4 of the crystal grains were tested, and the results are shown in Table 1.

[0092] [Table 1]

[0093] Example 1

[0094] (1) Mix the polyvalent positive electrode material P1 and cobalt hydroxide powder to obtain a mixture. The mixing equipment is a high-speed blender, and the linear velocity at the end of the mixing blade is 35 m / s. The polyvalent positive electrode material and cobalt hydroxide are added in a stoichiometric ratio of n(Co) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.025. The cobalt hydroxide powder contains nanometer-order and submicron-order particles at the same time, and its D50=0.5 μm, K90=2.3, and specific surface area is 20 m 2 / g. (2) The mixture is sintered at 750° C. for 6 hours in an oxygen atmosphere to obtain the single crystal type polyvalent positive electrode material A1, which includes a matrix and a coating layer coated on the matrix, and the matrix is ​​composed of Li 1.05 Ni 0.54 Co 0.18 Mn 0.18 Al 0.1 O2, the coating layer is mainly lithium cobalt oxide and also contains a small amount of cobalt oxide, and the molar ratio of the coating layer in terms of n(Co) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025.

[0095] Example 2

[0096] (1) Mixing the polyvalent positive electrode material P1 and tungsten oxide powder to obtain a mixture, using a high-speed blender as the mixing equipment, with a linear velocity at the end of the mixing blade of 35 m / s, adding the polyvalent positive electrode material P1 and tungsten oxide in a stoichiometric ratio of n(W) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.025, the tungsten oxide powder simultaneously contains nanometer-order and submicron-order particles, with D50=4 μm, K90=3.4, and a specific surface area of ​​14 m 2 / g. (2) The mixture is sintered at 750° C. for 6 hours in an oxygen atmosphere to obtain the single crystal type polyvalent positive electrode material A2, which includes a matrix and a coating layer coated on the matrix, and the matrix is ​​composed of Li 1.05 Ni 0.54 Co 0.18 Mn 0.18 Al0.1 O2, the coating layer is mainly lithium tungsten oxide and also contains a small amount of tungsten oxide, and the molar ratio of the coating layer in terms of n(W) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025.

[0097] Example 3 (1) Mixing the polyvalent positive electrode material P1 with titanium boride powder to obtain a mixture. The mixing equipment is a high-speed blender, and the linear velocity at the end of the mixing blade is 35 m / s. The positive electrode material and titanium boride are added in a stoichiometric ratio of n(Ti) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.025. The titanium boride powder contains nanometer-order and submicron-order particles at the same time, with D50=1 μm, K90=5.6, and a specific surface area of ​​45 m 2 / g. (2) The mixture is sintered at 750° C. for 6 hours in an oxygen atmosphere to obtain the single crystal type multivalent positive electrode material A3, which includes a matrix and a coating layer coated on the matrix, and the matrix is ​​composed of Li 1.05 Ni 0.54 Co 0.18 Mn 0.18 Al 0.1 O2, the coating layer is mainly lithium titanium oxide and also contains a small amount of titanium oxide, and the molar ratio of the coating layer in terms of n(Ti) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025.

[0098] Example 4 (1) Mix the polyvalent positive electrode material P1 with alumina powder to obtain a mixture. The mixing equipment is a high-speed blender. The linear velocity at the end of the mixing blade is 35 m / s. The positive electrode material and alumina are added in a stoichiometric ratio of n(Al) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.025. The alumina powder contains nanometer-order and submicron-order particles at the same time, with D50=3.8 μm, K90=2, and a specific surface area of ​​78 m. 2 / g. (2) The mixture is sintered at 750° C. for 6 hours in an oxygen atmosphere to obtain the single crystal type polyvalent positive electrode material A4, which includes a matrix and a coating layer coated on the matrix, and the matrix is ​​composed of Li 1.05 Ni 0.54 Co 0.18 Mn 0.18 Al 0.1 O2, the coating layer is mainly lithium aluminum oxide and also contains a small amount of aluminum oxide, and the molar ratio of the coating layer in terms of n(Al) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025.

[0099] Example 5 (1) Mixing the polyvalent positive electrode material P1 with alumina and zirconia powder to obtain a mixture, using a high-speed blender as the mixing equipment, and the linear velocity at the end of the mixing blade is 35 m / s. The alumina is added in a stoichiometric ratio of n(Al) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.025, and the zirconia is added in a stoichiometric ratio of n(Zr) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.025. The alumina powder contains nanometer-order and submicron-order particles, and its D50=3.8 μm, K90=2, and specific surface area is 78 m 2 / g, the zirconia powder contains nanometer-order and submicron-order particles, its D50=6 μm, K90=2.8, and specific surface area is 34 m 2 / g. (2) The mixture is sintered at 600°C for 8 hours in an oxygen atmosphere to obtain a single crystal type polyvalent positive electrode material A5, which includes a matrix and a coating layer coated on the matrix, and the matrix is ​​composed of Li 1.05 Ni 0.54 Co 0.18 Mn 0.18 Al 0.1O2, the coating layer mainly contains lithium aluminum oxide and lithium zirconium oxide, with small amounts of aluminum oxide and zirconium oxide, and the molar ratio of the coating layer in terms of [n(Al)+n(Zr)] to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.05, and in the coating layer, the molar ratio of the alumina and lithium aluminum oxide in terms of n(Al) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025, and the molar ratio of the zirconia and lithium zirconium oxide in terms of n(Zr) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025.

[0100] Example 6 A single crystal type multivalent positive electrode material was prepared by the method of Example 1, with the difference being that P2 was used instead of P1. A single crystal type multivalent positive electrode material A6 was obtained, which includes a matrix and a coating layer coated on the matrix. The matrix is ​​composed of Li 1.05 Ni 0.8 Co 0.1 Mn 0.1 Zr 0.002 O2, the coating layer is mainly lithium cobalt oxide and also contains a small amount of cobalt oxide, and the molar ratio of the coating layer in terms of n(Co) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Zr)] is 0.025.

[0101] Example 7 A single crystal type multivalent positive electrode material was prepared by the method of Example 1, with the difference being that P3 was used instead of P1. A single crystal type multivalent positive electrode material A7 was obtained, which includes a matrix and a coating layer coated on the matrix. The matrix is ​​composed of Li 1.03 Ni 0.96 Co 0.02 Al 0.02 Ti 0.001O2, the coating layer is mainly lithium cobalt oxide and also contains a small amount of cobalt oxide, and the molar ratio of the coating layer in terms of n(Co) to the matrix in terms of [n(Ni)+n(Co)+n(Al)+n(Ti)] is 0.025.

[0102] Example 8 A single crystal type multivalent positive electrode material was prepared by the method of Example 1, with the difference being that P4 was used instead of P1. A single crystal type multivalent positive electrode material A8 was obtained, which includes a matrix and a coating layer coated on the matrix. The matrix is ​​composed of Li 1.05 Ni 0.6 Co 0.2 Mn 0.2 O2, the coating layer is mainly lithium cobalt oxide and also contains a small amount of cobalt oxide, and the molar ratio of the coating layer in terms of n(Co) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)] is 0.025.

[0103] Example 9 A single crystal type multivalent positive electrode material was produced by the method of Example 1, with the difference being that the multivalent positive electrode material and cobalt hydroxide were added in a stoichiometric ratio of n(Co) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.001. A single crystal type multivalent positive electrode material A9 was obtained, which includes a matrix and a coating layer coated on the matrix, and the matrix was composed of Li 1.05 Ni 0.6 Co 0.2 Mn 0.2 O2, the coating layer is mainly lithium cobalt oxide and also contains a small amount of cobalt oxide, and the molar ratio of the coating layer in terms of n(Co) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)] is 0.001.

[0104] Example 10 A single crystal type multivalent positive electrode material was produced by the method of Example 1, except that the linear velocity at the end of the stirring blade was 10 m / s. A single crystal type multivalent positive electrode material A10 was obtained, which includes a matrix and a coating layer coated on the matrix. The matrix is ​​composed of Li 1.05 Ni0.54 Co 0.18 Mn 0.18 Al 0.1 O2, the coating layer is mainly lithium cobalt oxide and also contains a small amount of cobalt oxide, and the molar ratio of the coating layer in terms of n(Co) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025.

[0105] Example 11 A single crystal type multivalent positive electrode material was produced by the method of Example 1, except that the sintering temperature was 400° C. A single crystal type multivalent positive electrode material A11 was obtained, which includes a matrix and a coating layer coated on the matrix. The matrix is ​​composed of Li 1.05 Ni 0.54 Co 0.18 Mn 0.18 Al 0.1 O2, the coating layer is mainly lithium cobalt oxide and also contains a small amount of cobalt oxide, and the molar ratio of the coating layer in terms of n(Co) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025.

[0106] Example 12 A single crystal type multivalent positive electrode material was prepared by the method of Example 1, except that the sintering treatment time was 2 hours. A single crystal type multivalent positive electrode material A12 was obtained, which includes a matrix and a coating layer coated on the matrix. The matrix is ​​composed of Li 1.05 Ni 0.54 Co 0.18 Mn 0.18 Al 0.1 O2, the coating layer is mainly lithium cobalt oxide and also contains a small amount of cobalt oxide, and the molar ratio of the coating layer in terms of n(Co) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025.

[0107] Comparative Example 1 A single crystal type polyvalent positive electrode material was prepared by the method of Example 1, with the difference that the cobalt hydroxide powder contained only submicron order particles, D50=14 μm, K90=1, and a specific surface area of ​​6 m 2 A single crystal type multivalent positive electrode material D1 including a matrix and a coating layer covering the matrix is ​​obtained, and the matrix is ​​composed of Li 1.05 Ni 0.54 Co 0.18 Mn 0.18 Al 0.1 O2, the coating layer is mainly lithium cobalt oxide and also contains a small amount of cobalt oxide, and the molar ratio of the coating layer in terms of n(Co) to the matrix in terms of [n(Ni)+n(Co)+n(Mn)+n(Al)] is 0.025.

[0108] Comparative Example 2 Ni 0.6 Co 0.2 Mn 0.2 The (OH)2 precursor, lithium sources Li2CO3 and LiOH, and the Al-containing compound dopant were mixed in the molar ratios of n(Li) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=1.05 and n(Al) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.1, and then cobalt hydroxide powder was added in the molar ratio of n(Co) / [n(Ni)+n(Co)+n(Mn)+n(Al)]=0.025. The cobalt hydroxide powder contained nanometer-order and submicron-order particles at the same time, with D50=0.5μm, K90=2.3, and a specific surface area of ​​20m 2 / g, and heat treatment at 900 °C for 10 h was performed to obtain a multivalent positive electrode material D2, the composition of which is Li 1.05 Ni 0.53 Co 0.2 Mn 0.18 Al 0.09 It's O2.

[0109] [Table 2-1]

[0110] [Table 2-2]

[0111] Coexistence of G elements at different sites in the multivalent positive electrode materials of the manufacturing examples, examples, and comparative examples C1, C g , C2 (mol%) were tested, and the results are shown in Table 3.

[0112] In addition, in Table 3, when calculating whether the data meets the data ratio of formula II, the standard used is related to the content of G element. Specifically, when C1>5%, k ranges from 0.9 to 1.1; when C1≦5%, k ranges from 0.8 to 1.2.

[0113] [Table 3-1] [Table 3-2]

[0114] [Table 3-3]

[0115] [Table 3-4]

[0116] [Table 3-5]

[0117] [Table 3-6]

[0118] [Table 3-7]

[0119] [Table 3-8]

[0120] [Table 3-9]

[0121] Table 4 shows the coefficient k value calculated by Equation II at each site in the examples and comparative examples.

[0122] In addition, in Table 4, when calculating whether the data meets the data ratio of formula II, the standard used is related to the content of G element. Specifically, when C1>5%, k ranges from 0.9 to 1.1; when C1≦5%, k ranges from 0.8 to 1.2.

[0123] [Table 4-1]

[0124] [Table 4-2]

[0125] [Table 4-3]

[0126] [Table 4-4]

[0127] [Table 4-5]

[0128] [Table 4-6]

[0129] [Table 4-7]

[0130] [Table 4-8]

[0131] [Table 4-9]

[0132] FIG. 2 is a schematic diagram of the grain boundary stabilizer cobalt hydroxide containing micron and submicron ions. As can be seen from FIG. 2, the grain boundary stabilizer has a wide particle size distribution and a large difference in particle size. FIG. 3 is a cross-sectional schematic diagram of the single crystal type multivalent positive electrode material produced in Example 1. The numbers in the figure are examples of measurement sites for the concentration of elements within the grain boundaries.

[0133] The positive electrode materials of the Preparation Examples, Examples and Comparative Examples were assembled into lithium ion batteries, and the electrochemical performance of the lithium ion batteries was tested. The results are shown in the table below.

[0134] [Table 5]

[0135] As can be seen from Tables 3, 4 and 5, compared with Preparation Example 1 and Comparative Examples 1 and 2, the cathode materials prepared in Examples 1 to 12 of the present invention all contain an interface stabilizer element, and the concentration of G element at the g site of the grain boundary gradually decreases as the distance between the g site and the surface of the quasi-single crystal particle increases. When the cathode materials are used in lithium ion batteries, the initial discharge capacity, rate performance and cycling performance of the lithium ion batteries can be significantly improved, and the impedance increase rate can be reduced.

[0136] Furthermore, compared with Examples 9 to 12, the concentration gradient of the grain boundary stabilizer in the positive electrode materials prepared in Examples 1 to 8 at the grain boundaries is more significant, the gradient distribution is less uniform in Examples 9 to 12, the concentration at the surface of the material is higher, the difference in concentration closer to the inside of the particle is smaller, and some data is beyond the calculation range of Equation II. When the positive electrode materials prepared in Examples 1 to 8 are used in a lithium ion battery, the lithium ion battery can simultaneously have high first discharge specific capacity, rate performance, and cycling performance, and the impedance increase rate is lower, resulting in optimal overall battery performance.

[0137] Furthermore, Examples 2 to 4 show positive electrode materials prepared with different types of grain boundary stabilizers, all of which have good grain boundary concentration gradient filling effects. When the positive electrode materials are used in lithium ion batteries, they can improve the initial discharge capacity, rate performance, cycling performance and impedance increase rate of the lithium ion batteries.

[0138] Furthermore, Example 5 shows a positive electrode material prepared with two different types of grain boundary stabilizers, both of which have a concentration gradient filling effect, but since the total amount of grain boundary stabilizer added is larger, when used in a lithium ion battery, the battery capacity is slightly reduced, but the cycling performance is relatively better.

[0139] Furthermore, as can be seen from Examples 6 and 7, similar effects can be obtained for different NCM configurations. In Example 7, due to the low overall concentration, the range calculated by Formula II is narrow, which limits the test stability, and the percentage of sites that meet the calculated range is 89%. However, the relevant circumstances do not affect the judgment of the gradient concentration effect, and when used in lithium ion batteries, the effect improves and enhances various battery performances.

[0140] Moreover, as can be seen from Example 8, whether the positive electrode material is doped or not does not affect the improving effect of the grain boundary stabilizer on concentration gradient filling in the grain boundaries.

[0141] In the positive electrode material prepared in Comparative Example 1, the grain boundary stabilizer contains only micron-order particles, so the particle size distribution is narrow, the overall reaction activity is low, and the main element of the grain boundary stabilizer is abundant on the outer surface of the quasi-single crystal particles and cannot diffuse smoothly into the inside of the grain boundaries, so the effect of concentration gradient filling in the grain boundaries is not realized, and when used in a lithium ion battery, the overall performance expression is close to that of Preparation Example 1 and cannot reach the performance level of Example 1. Figure 4 is a comparison diagram of the cycling performance at 1C rate of the positive electrode materials prepared in Preparation Example 1, Example 1 and Comparative Example 1, and as can be seen from Figure 4, the difference in performance is significant.

[0142] In the positive electrode material prepared in Comparative Example 2, a grain boundary stabilizer was added at the stage of mixing the precursor and lithium salt, and then sintered. As can be seen from the results, there is no concentration difference between the surface and bulk phases, and there is no concentration gradient distribution effect at the grain boundaries. When used in a lithium ion battery, the performance expression does not have a significant improvement effect compared to Preparation Example 1.

[0143] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited thereto. Within the technical scope of the present invention, the technical solutions of the present invention may be modified in various simple ways, including combining each technical feature in any other suitable manner, and these simple modifications and combinations are also considered as the contents disclosed in the present invention, and all belong to the protection scope of the present invention.

Claims

1. A single-crystal polyvalent positive electrode material, the single-crystal polyvalent positive electrode material including quasi-single-crystal particles formed of a plurality of crystal grains, and a G element being present at grain boundaries between the crystal grains; The concentration of G elements at the g sites of the grain boundaries gradually decreases as the distance between the g sites and the surface of the quasi-single crystal grain increases. The G element is selected from at least one of Ni, Co, Mn, Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, and B; Preferably, the G element is at least one selected from the group consisting of Mn, Co, W, La, Al, Ti, Zr and Nb.

2. In the SEM image of the cross-sectional sample of the quasi-single crystal grain, the concentration of the G element at the g site of the grain boundary satisfies the following relationship: 1.2C 1 ≧C g ≧0.8C 2 Formula I [0010] C 1 is the concentration (mol%) of the G element on the surface of the quasi-single crystal particle, and C 2 is the concentration (mol%) of the G element in the bulk phase of the quasi-single crystal particle, and C g is the concentration (mol%) of the G element at the g site of the grain boundary, L is the total length (μm) of the grain boundary passing through the g site, and L g is the shortest path length (μm) from the g site along the grain boundary to the surface of the quasi-single crystal particle, k is a coefficient, and k has a value range of 0.8 to 1.

2. The monocrystalline polyvalent positive electrode material according to claim 1.

3. 1.1C 1 ≧C g ≧0.9C 2 The monocrystalline polyvalent positive electrode material according to claim 1 or 2,

4. the total length L of the grain boundary obtained by spectroscopic analysis using a scanning electron microscope satisfies 0.01 μm≦L≦8 μm, preferably 0.1 μm≦L≦5 μm; Preferably, C 1 -C 2 ≧0.1%, more preferably 1 -C 2 ≧0.2%, Preferably, C 1 >5%, the value range of k is 0.9 to 1.1, and C 1 4. The monocrystalline polyvalent positive electrode material according to claim 2 or 3, wherein k is in the range of 0.8 to 1.2 when ≦5%.

5. The major axis D of the quasi-single crystal particle 1 0.1 μm≦D 1 ≦20 μm, and the minor axis D 2 0.1μm≦D 2 ≦20 μm, Preferably, the major axis D of the crystal grain 3 0.1 μm≦D 3 ≦12 μm, and the minor axis D 4 0.1μm≦D 4 ≦12 μm, Preferably, the grain boundary has a width of 1 to 50 nm, and the difference between the maximum value of the grain boundary width and the minimum value of the grain boundary width is 20 nm or less. The single crystal type polyvalent positive electrode material according to any one of claims 1 to 4.

6. The single crystal polyvalent positive electrode material includes a matrix and a coating layer that is coated on the matrix, The matrix has the configuration as shown in Formula III: Li 1+a (Ni x Co y Me z M w )O 2 Formula III -0.1≦a≦0.1, 0<x<1, 0<y≦0.4, 0<z≦0.6, 0≦w≦0.2, Me is selected from Mn and / or Al, and M is at least one element selected from Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, and Ba; the coating layer is selected from lithium oxygen compounds of G elements and / or oxides of G elements; G is at least one element selected from the group consisting of Ni, Co, Mn, Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, and B; the molar ratio of the coating layer in terms of n(G) to the matrix in terms of [n(Ni)+n(Co)+n(Me)+n(M)] is 0.001 to 0.05; Preferably, −0.06≦a≦0.06, 0.4<x<1, 0<y≦0.3, 0<z≦0.5, and 0<w≦0.1; Preferably, Me is selected from Mn and / or Al, M being at least one element selected from W, La, Al, Y, Ti, Zr, Nb, Ce, Mg and Sr; Preferably, G is at least one element selected from the group consisting of Mn, Co, W, La, Al, Ti, Zr and Nb; Preferably, the molar ratio of the coating layer in terms of n(G) to the matrix in terms of [n(Ni) + n(Co) + n(Me) + n(M)] is 0.005 to 0.

04. The monocrystalline polyvalent positive electrode material according to any one of claims 1 to 5.

7. A method for producing a monocrystalline polyvalent positive electrode material, the method comprising the steps of: The method includes a step of mixing a multivalent positive electrode material matrix with a grain boundary stabilizer containing a G element, and then sintering the mixture to obtain the single crystal multivalent positive electrode material; The G element is selected from at least one of Ni, Co, Mn, Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, and B; A method for producing a single crystal type polyvalent positive electrode material, characterized in that D50 of the grain boundary stabilizer is 0.01 to 10 μm, and D10, D50, and D90 of the grain boundary stabilizer satisfy K90 = (D90 - D10) / D50 ≧ 1.

5.

8. The G element is selected from at least one of Mn, Co, W, La, Al, Ti, Zr, and Nb, Preferably, the grain boundary stabilizer is selected from at least one of oxides, oxyhydroxides, hydroxides, fluorides, sulfates, nitrates, carbonates, and oxalates containing a G element; Preferably, the grain boundary stabilizer has a D50 of 0.1 to 8 μm, and the D10, D50, and D90 of the grain boundary stabilizer satisfy K90=(D90-D10) / D50≧2; Preferably, the specific surface area of ​​the grain boundary stabilizer is 10 m 2 / g or more, preferably 20 to 100m 2 The method according to claim 7, wherein the molecular weight is 1 / g.

9. The grain boundary stabilizer is added in an amount such that the stoichiometric ratio is 0.001≦n(G) / [n(Ni)+n(Co)+n(Me)+n(M)]≦0.05, and preferably, the amount added is 0.005≦n(G) / [n(Ni)+n(Co)+n(Me)+n(M)]≦0.04; Preferably, the mixing conditions include mixing in equipment including a stirring paddle, and the linear velocity of the end of the blade of the stirring paddle is 20 m / s or more, preferably 30 to 50 m / s; Preferably, the sintering conditions include a sintering temperature of 400° C. or more, preferably 600-900° C., and a sintering time of 4 h or more, preferably 6-10 h. The manufacturing method according to claim 7 or 8.

10. The polyvalent positive electrode material matrix has a configuration as shown in Formula IV: Li 1+a (Ni x Co y Me z M w )O 2 Formula IV wherein -0.1≦a≦0.1, 0<x<1, 0<y≦0.4, 0<z≦0.6, and 0≦w≦0.2, Me is selected from Mn and / or Al, and M is at least one of Ta, Cr, Mo, W, La, Al, Y, Ti, Zr, V, Nb, Ce, Er, Mg, Sr, and Ba; Preferably, −0.06≦a≦0.06, 0.4<x<1, 0<y≦0.3, 0<z≦0.5, and 0<w≦0.1; Preferably, Me is selected from Mn and / or Al, The method according to any one of claims 7 to 9, wherein M is at least one of W, La, Al, Y, Ti, Zr, Nb, Ce, Mg, and Sr.

11. A single crystal type polyvalent positive electrode material produced by the method according to any one of claims 7 to 10.

12. A lithium ion battery comprising the single crystal polyvalent positive electrode material according to any one of claims 1 to 6 and 11.

Citation Information

Patent Citations

  • Ternary positive electrode material, preparation method thereof and lithium ion battery

    CN112803010A

  • Single-crystal type multi-element positive electrode material as well as preparation method and application thereof

    CN114703544A

  • Ternary positive electrode material with low gas generation and high capacity

    US20220085378A1

  • Single-crystal-type multi-element positive electrode material, and preparation method therefor and application thereof

    WO2022207008A1